Histone 3 s10 phosphorylation: "caught in the R loop!". - Skourti-Stathaki, K; Proudfoot, N (2013)
In this issue of Molecular Cell, Castellano-Pozo et al. (2013) describe a connection between R loop structures and histone 3 S10 phosphorylation (H3S10P), a mark of chromatin compaction. Their results constitute a significant advance in our understanding of the role of R loops in genomic instability.